CLIMATE-INDUCED GLACIAL LAKE OUTBURST FLOODS: CHALLENGES AND POLICY RESPONSES IN PAKISTAN - Hamad Ullah; Jana Awez; Areeba Falak; Tayyaba Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Nine major river systems in Asia receive their headwaters from glaciers, which act as a freshwater reserve and as a lifeline for nearly one third of humanity. The melting of glaciers in recent decades has been demonstrated by tons of evidence. As a result of glacial retreat, more and larger glacial lakes are forming at the new terminal ends, hidden behind the exposed end moraines. Due to these, there is a greater chance that glacial lake outburst floods (GLOF) will occur. Climate change is one of the major reasons for the glacial lake outburst flood. Glaciers and high-mountain ecosystems have been greatly impacted by recent warming. Especially Countries that are more exposed to climate change are more vulnerable to GLOF. Pakistan is one of the countries that is facing climate change issues. This country hosts the world’s third largest glacial ice mass, and extreme weather conditions (i.e., from winters to scorching summers and heat waves) in the country often result in catastrophic floods, such as those seen in the second half of 2022, where unprecedented floods occurred as a result of GLOF. The objective of our paper is to evaluate Pakistan’s current climate change policy and to oversee the challenges faced by authorities in getting rid of torrential floods. Did Pakistan adopt the policies needed to overcome the floods? If it did, then what are the main causes of its outburst, and where do we lack in policy implementation that needs to be changed? In this study, we assess the extent of the GLOF threat in Pakistan, its impact on the country’s people, water security, and economy, and the necessary adjustments to either mitigate or prevent it.